Antihyperglycemic, antihyperlipidemic, and antioxidant effects of Eclipta prostrata L. aqueous extract in streptozotocin-induced diabetic rats - Zhang, Lingming; Zheng, Chao; Xu, Tongdao; Liang, Du (Penerbit Universiti Kebangsaan Malaysia, 2022)
With the rising prevalence of diabetes mellitus around the world, researchers have been searching for a new treatment option that is both more effective and safer than chemotherapy. This study evaluated the antidiabetic activities of aqueous extracts of Eclipta prostrata L. in streptozotocin (STZ)-induced diabetic rats. The rats were randomized into six groups: Normal control, STZ-induced diabetic rats (50 mg/kg), STZ+EPE (100 mg/kg), STZ + EPE (200 mg/kg), STZ+glibenclamide (600 µg/kg) and EPE alone (200 mg/kg). The STZ-induced diabetic rats showed significantly (p<0.05) elevated glucose, HbA1c, lipid profile, hepatic, and kidney markers, while significantly (p<0.05) decreased insulin levels. The changes in activities of carbohydrate metabolizing enzymes such as glucose-6-phosphatase, fructose-1,6–bisphosphatase were significantly (p<0.05) increased in diabetic rats, while the activity of glucokinase and glucose-6-phosphate dehydrogenase were significantly (p<0.05) reduced. Oral treatment of STZ-induced diabetic rats with E. prostrata (100 and 200 mg/kg) and glibenclamide (600 µg/kg) prevented the alteration as mentioned earlier and brought back them to near normalcy. The current findings in experimental diabetic rats suggest that oral treatment with E. prostrate ameliorated carbohydrate metabolizing enzymes, showed total cholesterol-lowering effects, improved serum high-density lipoprotein (HDL) cholesterol levels and exhibited intriguing antioxidant activities.